2017
DOI: 10.3390/nu9060616
|View full text |Cite
|
Sign up to set email alerts
|

Iron Deficiency Anemia as a Risk Factor for Osteoporosis in Taiwan: A Nationwide Population-Based Study

Abstract: The cause-effect relationship between iron deficiency anemia (IDA) and osteoporosis has not been established in the general population. Thus, the current longitudinal study determined the role of IDA as a risk factor for osteoporosis by analyzing a large nationwide population-based sample. In a sample of 1,000,000 randomly sampled individuals from the 1998–2012. Taiwan National Health Insurance Research Database, patients with IDA (case group (n = 35,751)) and individuals without IDA (control group (n = 178,75… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 24 publications
3
27
0
1
Order By: Relevance
“…One of the limitations of the study was that subjects with hormone replacement, osteoporosis treatment or hysterectomy were excluded. Pan et al (2017) reported similar findings on the association between IDA and osteoporosis in the general population but their results were not gender specific. Also, in Harris et al (2003 reported that the dietary intake of iron is positively associated with mineral bone density in postmenopausal woman aged between 44 and 66 years.…”
Section: Accepted Manuscriptsupporting
confidence: 54%
“…One of the limitations of the study was that subjects with hormone replacement, osteoporosis treatment or hysterectomy were excluded. Pan et al (2017) reported similar findings on the association between IDA and osteoporosis in the general population but their results were not gender specific. Also, in Harris et al (2003 reported that the dietary intake of iron is positively associated with mineral bone density in postmenopausal woman aged between 44 and 66 years.…”
Section: Accepted Manuscriptsupporting
confidence: 54%
“…Our results are in line with numerous evidences of multidirectional (patho)physiological links between the skeleton as a dynamic, metabolically active organ and the cardiovascular, renal, liver, endocrine, nervous and immune systems. Our observations complement the results from many previous studies showing positive bi- and multi-directional relationships between osteoporosis, falls and fractures, on one hand, and chronic conditions such as CKD 71 , 85 - 90 , CVDs 91 - 104 , anaemia 105 - 111 , hypoalbuminaemia 112 - 114 and hyperthyroidism 115 - 119 on the other, supporting the concept that osteoporosis is a systemic disease.…”
Section: Discussionsupporting
confidence: 89%
“…First, anemia itself is related to low bone density. A large cohort study in Taiwan reported that the risk of osteoporosis was significantly higher in subjects with iron‐deficient anemia (IDA) than in those without IDA . The MROS study found that bone mineral density (BMD) loss over time was associated with anemia .…”
Section: Discussionmentioning
confidence: 99%